Digital signal processing applications in monophonic music analysis - Guevara, Rowena Cristina L. (1990)
The applicability of different Digital Signal Processing (DSP) techniques in extracting the pitch, instrument identity and note duration of musical signals was investigated. Based on this, an algorithm for decomposing and analyzing monophonic music was developed. The resulting program is basically a guided, continuous, overlapped Fast Fourier Transform, applicable to analysis of monophonic music generated by any pitched instrument.
Typescript.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Signal processing -- Digital techniques; Musical pitch